Rancangan Manajemen Talenta Guru Pada Lembaga Pendidikan Anak Langit - Muhammad Idzhar Faisa; Joeliaty Joeliaty (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
The present study explores the implementation of talent management at Anak Langit Educational Institution, aiming to design a comprehensive talent management framework tailored to the organization's unique needs. The research uses a qualitative approach to identify talent criteria, assess selection methods, and examine on-boarding, development, and retention practices. The findings reveal that Anak Langit demonstrates a strong commitment to shaping a 'rabbani' generation through structured talent management practices. The institution actively engages in recruitment using various methods, including social media promotion and campus relations. Talent development primarily consists of workshops and training programs, with opportunities for individual skill enhancement. Performance evaluation extends beyond job performance to personal development and interpersonal skills. In talent retention efforts, Anak Langit provides informal appreciation, support, and work-life balance programs. However, the study suggests opportunities for further development, such as the creation of detailed talent management guidelines for transparency and effectiveness. The comprehensive talent management framework proposed includes specific talent criteria, a Talent Development Center, Key Performance Indicators (KPIs) implementation, and flexible individual development plans, ensuring a structured, flexible, and individual-focused approach.